Sacred leaves of Candomblé: African magic, medicine, and religion in Brazil - Voeks, Robert A. (University of Texas Press, 1997)
"Thorough ethnobotanical study of the origin, diffusion, use, classification, and cultural significance of Afro-Brazilian sacred plants"--Handbook of Latin American Studies, v. 57